Strategi Komunikasi Pemasaran Digital CV. Taha Citra Mobil Dalam Meningkatkan Penjualan Mobil diKota Medan - Sugiharto, Rizky; Jailani, M (Asosiasi Ide Bahasa Kepri, 2024)
This research discusses digital marketing communication strategies on CV. Taha Car Image. CV is an abbreviation of Commanditaire Vennootschap, in Indonesian it is also called Commander's Fellowship. This research aims to observe strategies that can increase sales carried out by the company. CV. Taha Citra Mobil is one of the CVs that operates in the field of buying/selling used cars, which can create a positive impact between parties to build long relationships, consumers and stakeholders. This research uses qualitative methods with interviews and analysis to gain a competent understanding of the digital marketing communication strategy implemented by Taha Citra. The research results prove that the strategy can be implemented perfectly by involving consumers through social media and e-commerce platforms, displaying creative, innovative content and existing facts and establishing cooperative relationships. It is known that the use of functional tools is very useful for measuring the extent of marketing effectiveness. According to these findings, it is hoped that competitors can provide updated activities on digital platforms through the media, establishing good relationships with consumers by providing content that is educational and interesting. Therefore, this research provides benefits for competitors to develop more innovative marketing communication strategies in the future.